ACCOUNTING INFORMATION AS THE BASIS FOR STRATEGIC MANAGEMENT OF AGRICULTURAL ENTERPRISES - Milojević, Ivan; Krstić, Dalibor; Bukovala, Jovan (Economics of Agriculture, 2021)
A key place in economic theory belongs to learning about the position of immediate creators, i.e. producers of goods in every socio-economic formation. This position and all relations in production and society depend significantly on the historical form of production of excess work and the way of appropriating excess work. Therefore, for analysis of the modern way of commodity agroproduction, it is necessary to dispose of information that is the basis for decision-making at the strategic level. This type of information is characterized by the accounting information system as one of the main sources of business information. For the subject of this work, we will take the modern way of agroproduction and creation of excess value, which in recent times, especially after the global economic crisis, is gaining increasing significance in both economic theory and economic reality.